Cytotoxicity evaluation of tricalcium phosphate on human osteoblast cell line - Dasmawati, Mohamad (Pusat Pengajian Sains Perubatan, 2012)
The aim of the study was to determine the biocompatibility of II-Tricalcium Phosphate (JI-TCP) prepared by hydrothermal and precipitation method with normal human osteoblast (NHOst) cells. For this purpose, cytotoxicity of the material was assessed using an Alamat Blue method to determine the viability ofNHOst cells grown with extracts of II-TCP in various concentrations. In addition NHOst grown on II-TCP ceramics were examined under an inverted microscope after 4, 24, 48 and 72 hours to verifY cell attachment. Staining was done using Calcein AM and Ethidium homodimers to assess viability using a Confocal Laser Scanning Microscope (CLSM). The results showed that neither hydrothermal II-TCP nor precipitation 11-TCP were cytotoxic with either of the method applied.